The Influence Of Consumer Interest, Price On Business Development And Sales Of Palembang Songket - Hurian Kamela (LP2M IAIN Palopo, 2026)
Purpose – This study aims to analyze consumer interest, pricing, and business development strategies of songket in Palembang, while also identifying the obstacles in its management. Palembang songket is a highly valuable cultural heritage but faces challenges in maintaining its existence amid modern product competition. The urgency of this research lies in the limited number of studies exploring local cultural values from marketing and business perspectives. The novelty of this study lies in its mixed-method approach, combining buyer and seller perspectives through interviews and surveys. Data were collected through questionnaires distributed to 60 songket consumers in Palembang, as well as interviews with songket business owners. The analysis technique uses a mixed-method approach (interviews and regression testing). The results show that consumer interest is influenced by perceptions of product quality and pricing, along with a positive tendency towards design development that remains rooted in traditional values. The main barriers in managing the songket business include lack of promotion, limited capital, and low artisan regeneration. Although limited to a specific geographical area, this study serves as a strategic reference for policymakers, industry practitioners, and academics in supporting the sustainability of the Palembang songket industry.